Analysis of Spectrum Characteristics of Audible Noise Generated by AC Corona Discharge - Mingxiang HUANG; Zhibin GUO; Lizhi PAN; Xuebao LI (Zhongguo dianli)
The audible noise (AN) generated by alternative current (AC) corona discharge is mainly composed of wide frequency band and pure tones at harmonics of power frequency. In order to understand the distinct spectrum characteristics of AN, the time-domain waveforms of AN occurring on the surface of conductor are measured using the time-domain test platform for AC corona-generated audible noise. Based on the analysis of its time and frequency characteristics, the AN is divided into three components: impulsive noise, ion-migration noise and background noise, and a wavelet-transform based noise extraction method is proposed to separate them. The impact mechanism of the AC voltage modulation and space ion-migration on conductor pure tones as well as the variation characteristics of pure tones are obtained. The result shows that under the effect of AC voltage modulation, the periodic pulse cluster noise and the reciprocating migration noise of space ions constitute the pure tones, while the ion migration has larger effects than the voltage modulation. The pure tones become prominent with the increase of voltage and share more proportion of the total sound pressure level. Finally, the motion characteristics of space ions in the process of corona discharge are presented to give a qualitative explanations for the spectrum characteristics of AN.